Moisture-curing hot melt adhesive

A moisture-curable hot melt adhesive with a tailored blend of polyols and a polyisocyanate reactant addresses the challenge of balanced initial and normal adhesion, ensuring effective bonding and easy peeling on non-porous substrates.

JP7660878B2Active Publication Date: 2025-04-14SEKISUI FULLER CO LTD
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
JP2021058854
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-30
Publication Date
2025-04-14
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Existing moisture-curable hot melt adhesives face challenges in achieving balanced initial adhesion and peeling properties, especially on non-porous substrates with smooth surfaces, which can lead to partial peeling off and difficulties in reusing substrates.

Method used

The adhesive composition includes a specific blend of polyols such as crystalline polyester polyol, microcrystalline polyester polyol, non-crystalline polyester polyol, and polyether polyol, along with a polyisocyanate reactant to form a urethane prepolymer that cures through moisture, optimizing initial and normal adhesion properties.

Benefits of technology

This composition achieves excellent initial adhesion to maintain the decorative sheet on the substrate's surface, while also ensuring easy peeling and reuse of the substrate, even on non-porous substrates with smooth surfaces, and maintains strong normal adhesion after curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660878000001
    Figure 0007660878000001
  • Figure 0007660878000002
    Figure 0007660878000002
Patent Text Reader

Abstract

To provide a moisture-curable hot melt adhesive excellent in initial adhesiveness, initial releasability and normal adhesiveness.SOLUTION: A moisture-curable hot melt adhesive of the present invention contains a urethane prepolymer that has an isocyanate group at the end thereof and is a reaction product of a polyisocyanate and polyols including: a crystalline polyester polyol which is a condensation polymer of a polycarboxylic acid having a predetermined carbon number and a polyol having a predetermined carbon number; a microcrystalline polyester polyol having a predetermined number average molecular weight; an amorphous polyester polyol having a predetermined number average molecular weight; and a polyether polyol having a predetermined number average molecular weight. The polyols contain the crystalline polyester polyol, the microcrystalline polyester polyol, the amorphous polyester polyol, and the polyether polyol in predetermined amounts respectively.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a moisture-curable hot melt adhesive. [Background technology]

[0002] 2. Description of the Related Art Conventionally, decorative sheets have been attached to the surfaces of substrates such as furniture, exterior materials, and interior materials using moisture-curing hot melt adhesives to impart design features.

[0003] Patent Document 1 discloses a moisture-curing adhesive containing a urethane prepolymer having an isocyanate group, the urethane prepolymer having an isocyanate group being a reaction product of polyol (A) and polyisocyanate (B), and the polyol (A) containing a polycarbonate polyol (a1) having a unit derived from a hydroxy compound (d1) represented by a specific structural formula. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-44005 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the process of bonding a decorative sheet to the surface of a substrate via an adhesive, immediately after the decorative sheet is placed on the surface of the substrate, the decorative sheet needs to be held in a state conforming to the surface of the substrate via the adhesive (initial adhesion).

[0006] With the above-mentioned moisture-curing adhesive composition, if the surface shape of the substrate is complex or if the surface of the substrate is smooth with few irregularities, immediately after the decorative sheet is placed on the substrate surface, the decorative sheet will return to its original state due to its elastic recovery force before the moisture-curing adhesive composition can exert sufficient initial adhesive strength, resulting in the problem that the decorative sheet will be partially peeled off from the surface of the substrate.

[0007] One possible solution is to increase the initial adhesive strength of the adhesive, but this can cause some problems in the process of attaching the decorative sheet to the surface of the substrate via the adhesive, and in such cases, it is necessary to peel the decorative sheet from the surface of the substrate (initial releasability).In particular, in the case of non-porous substrates made of synthetic resins such as polystyrene, composite-coated aluminum (aluminum that has been anodized and then surface-treated such as painted), etc., where the substrate surface has few irregularities and is formed into a smooth surface, initial releasability is highly desired.

[0008] If the initial adhesion of the adhesive is too high, when the decorative sheet is peeled off from the surface of the substrate, solidified adhesive remains on the surface of the substrate, and unless this remaining adhesive is removed with a solvent or the like, the substrate cannot be reused, which creates other problems such as an increase in the reject rate and a decrease in productivity.

[0009] On the other hand, if the initial adhesive strength of the adhesive is reduced, not only will the initial adhesiveness described above decrease, but the adhesiveness after the adhesive has hardened (normal adhesiveness) will also decrease, resulting in the problem that the decorative sheet that has been bonded and integrated to the surface of the substrate will easily peel off from the substrate surface during subsequent use.

[0010] Thus, the adhesive that bonds and integrates the decorative sheet to the substrate must have contradictory requirements immediately after the decorative sheet is placed on the substrate surface and when the decorative sheet is bonded and integrated to the substrate surface.

[0011] The present invention provides a moisture-curing hot melt adhesive that has excellent initial adhesion and initial peelability immediately after a surface sheet, such as a decorative sheet, is bonded to the surface of a substrate via the adhesive, while also having excellent normal-state adhesion that enables the surface sheet to be firmly bonded and integrated to the surface of the substrate after curing.

[0012] In particular, the present invention provides a moisture-curing hot melt adhesive that has excellent initial adhesion and initial peelability even on non-porous substrates whose surfaces are formed into a smooth surface with few irregularities, while also having excellent normal-state adhesion that enables a surface sheet to be firmly adhered and integrated to the surface of the non-porous substrate after curing. [Means for solving the problem]

[0013] The moisture-curable hot melt adhesive of the present invention contains a urethane prepolymer which is a reaction product of a polyol including a crystalline polyester polyol which is a condensation polymer of a polycarboxylic acid having 2 to 14 carbon atoms excluding the carbon in the carboxy group and a polyol having 2 to 8 carbon atoms, a microcrystalline polyester polyol having a number average molecular weight of 3000 to 6000, a non-crystalline polyester polyol having a number average molecular weight of 3000 to 6000, and a polyether polyol having a number average molecular weight of 500 to 7000, and a polyisocyanate and has an isocyanate group at its terminal; When the total amount of the crystalline polyester polyol, the microcrystalline polyester polyol, the non-crystalline polyester polyol, and the polyether polyol is taken as 100 mass %, The polyol is characterized by containing 15 to 35% by mass of the crystalline polyester polyol, 20 to 50% by mass of the microcrystalline polyester polyol, 10 to 50% by mass of the non-crystalline polyester polyol, and 5 to 30% by mass of the polyether polyol. Effect of the Invention

[0014] The moisture-curable hot melt adhesive of the present invention has excellent initial adhesion, which allows the surface sheet to be maintained in a state that conforms to the shape of the substrate surface immediately after the surface sheet is disposed on the substrate surface via the moisture-curable hot melt adhesive. In particular, the moisture-curable hot melt adhesive of the present invention has excellent initial adhesion even to substrates (e.g., non-porous substrates) that have a smooth surface with few irregularities, such as metal substrates and synthetic resin substrates.

[0015] As described above, the moisture-curing hot melt adhesive of the present invention has excellent initial adhesion, while immediately after a surface sheet is placed on the surface of a substrate via the moisture-curing hot melt adhesive, the surface sheet can be easily peeled off from the surface of the substrate, making it easy to reuse the substrate (initial releasability).

[0016] In particular, the moisture-curable hot melt adhesive of the present invention has excellent initial adhesion, even on substrates having smooth surfaces with few irregularities, while also having excellent initial peelability.

[0017] Furthermore, the moisture-curing hot melt adhesive of the present invention has excellent normal state adhesion that enables the surface sheet to be firmly adhered and integrated to the surface of the substrate (especially the surface of a substrate having a smooth surface with few irregularities) after laminating the surface sheet to the surface of the substrate and curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The moisture-curable hot melt adhesive of the present invention contains a urethane prepolymer which is a reaction product of a polyol containing a specific polyol and a polyisocyanate and has an isocyanate group at its end. The urethane prepolymer cures by a crosslinking reaction caused by moisture contained in the air and / or the substrate.

[0019] The reaction between the polyol and the polyisocyanate may be carried out in a general manner. For example, the polyisocyanate is charged into a reaction vessel, and the polyol from which moisture has been removed in advance is dropped into the reaction vessel, either separately or after mixing with additives, and the hydroxyl group and the isocyanate group are reacted in a heated state. Alternatively, the polyol and additives are charged into a reaction vessel, and the polyol and additives are heated, melted, and dispersed, and then moisture is removed, and then the polyisocyanate is charged to carry out the reaction between the hydroxyl group and the isocyanate group. The production of the urethane prepolymer can usually be carried out without a solvent, but can also be carried out in a solvent that does not inhibit the reaction. Specific examples of the solvent include, for example, butyl acetate, methyl ethyl ketone, and toluene. In the reaction between the hydroxyl group of the polyol and the isocyanate group of the polyisocyanate, a urethane catalyst can be used as necessary. The urethane catalyst is not particularly limited, and examples thereof include triethylamine, triethylenediamine, N-methylmorpholine, potassium acetate, zinc stearate, tin octoate, and dibutyltin dilaurate. The urethane or catalyst may be used alone or in combination of two or more. A polymeric isocyanate having more than two isocyanate groups in one molecule (e.g., polymethylene polyphenyl polyisocyanate, crude toluene polyisocyanate, etc.) is preferably used in combination with a diisocyanate in order to reduce the melt viscosity of the moisture-curing hot melt adhesive. After a part of a polyol is reacted with a diisocyanate in the above-mentioned manner to produce a urethane prepolymer, a polymeric isocyanate having more than two isocyanate groups in one molecule may be added to the reaction system and reacted with the polyol to produce a urethane prepolymer.

[0020] In the reaction between the polyol and the polyisocyanate, the ratio of the number of moles of hydroxyl groups in the polyol to the number of moles of isocyanate groups in the polyisocyanate (number of moles of isocyanate groups / number of moles of hydroxyl groups) is preferably 1.3 to 4.0, more preferably 1.5 to 3.0. When the molar ratio is 1.5 or more, the applicability of the moisture-curable hot melt adhesive is improved. When the molar ratio is 3.0 or less, the initial peelability of the moisture-curable hot melt adhesive is improved.

[0021] [Polyol] The urethane prepolymer contained in the moisture-curable hot melt adhesive is a reaction product of a polyol (A) containing a specific polyol and a polyisocyanate (B). The urethane prepolymer has an isocyanate group at the molecular end, and preferably has an isocyanate group at both molecular ends.

[0022] The polyol (A) contains a crystalline polyester polyol (A1), a microcrystalline polyester polyol (A2), a non-crystalline polyester polyol (A3) and a polyether polyol (A4), which will be described later.

[0023] In the polyol (A), the total amount of the crystalline polyester polyol (A1), the microcrystalline polyester polyol (A2), the non-crystalline polyester polyol (A3) and the polyether polyol (A4) is preferably 50 mass% or more, more preferably 60 mass% or more, more preferably 70 mass% or more, more preferably 80 mass% or more, more preferably 90 mass% or more, and particularly preferably 100 mass%.

[0024] [Crystalline polyester polyol (A1)] The crystalline polyester polyol (A1) is a condensation polymer of a polycarboxylic acid having 2 to 14 carbon atoms excluding the carbon in the carboxy group (-COOH) and a polyol having 2 to 8 carbon atoms. That is, the crystalline polyester polyol (A1) is a polymer obtained by condensation polymerization of a polycarboxylic acid having 2 to 14 carbon atoms excluding the carbon in the carboxy group and a polyol having 2 to 8 carbon atoms by esterification at the carboxyl group of the polycarboxylic acid and the hydroxyl group of the polyol. The condensation polymerization reaction of the polycarboxylic acid and the polyol may be carried out using a general-purpose method. The number of carbon atoms excluding the carbon in the carboxy group, which is specified for the polycarboxylic acid, refers to the number of carbon atoms obtained by subtracting the total number of carbons in all carboxy groups from the total number of carbons contained in the molecule.

[0025] In the polycarboxylic acid, the number of carbon atoms excluding the carbon in the carboxy group is 2 to 14, preferably 10 to 12. When the number of carbon atoms excluding the carbon in the carboxy group is 2 or more, the crystallinity of the crystalline polyester polyol (A1) is improved, and the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. When the number of carbon atoms excluding the carbon in the carboxy group is 14 or less, the normal adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable.

[0026] Polycarboxylic acids are divalent carboxylic acids (HOOC-R 1 -COOH). If it is a divalent carboxylic acid, the melt viscosity of the moisture-curable hot melt adhesive can be reduced. 1 R has 2 to 14 carbon atoms, and more preferably 10 to 12 carbon atoms. 1 When the number of carbon atoms is within the above range, the initial adhesiveness of the moisture-curable hot melt adhesive is improved.

[0027] R 1 R is preferably an aliphatic chain, more preferably a linear aliphatic chain. 1 When R is an aliphatic chain, the crystallinity of the crystalline polyester polyol (A1) is improved, and the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. 1When R is linear, the crystallinity of the crystalline polyester polyol (A1) is improved, and the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. 1 R is linear means that the carbon atoms are bonded in a straight line without branching. 1 is preferably a linear alkylene group (-CnH2n-), where n is a natural number.

[0028] The polycarboxylic acid having 2 to 14 carbon atoms excluding the carbon in the carboxy group (-COOH) is not particularly limited, and examples thereof include sebacic acid, decamethylenedicarboxylic acid (1,10-decanedicarboxylic acid), 1,14-tetradecanedicarboxylic acid, etc., with sebacic acid and decamethylenedicarboxylic acid being preferred. The polycarboxylic acid may be used alone or in combination of two or more kinds.

[0029] The carbon number of the polyol is 2 to 8, preferably 2 to 6. When the carbon number of the polyol is 2 or more, the crystallinity of the crystalline polyester polyol (A1) is improved, and the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. When the carbon number of the polyol is 8 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced, which is preferable.

[0030] Polyols are dihydric alcohols (HO-R 2 -OH). If it is a dihydric alcohol, the melt viscosity of the moisture-curable hot melt adhesive can be reduced. 2 The number of carbon atoms in R is preferably 2 to 8, and more preferably 2 to 6. 2 When the number of carbon atoms is within the above range, the initial adhesiveness of the moisture-curable hot melt adhesive is improved.

[0031] R 2 R is preferably an aliphatic chain, more preferably a linear aliphatic chain. 2 When R is an aliphatic chain, the crystallinity of the crystalline polyester polyol (A1) is improved, and the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. 2When R is linear, the crystallinity of the crystalline polyester polyol (A1) is improved, and the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. 2 R is linear means that the carbon atoms are bonded in a straight line without branching. 2 is preferably a linear alkylene group (-CmH2m-), where m is a natural number. m is preferably an even number, since this improves the crystallinity of the crystalline polyester polyol (A1) and improves the initial adhesiveness of the moisture-curable hot melt adhesive.

[0032] The polyol having 2 to 8 carbon atoms is not particularly limited, and examples thereof include 1,2-ethanediol (ethylene glycol), 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, and 1,8-octanediol, with 1,6-hexanediol and 1,2-ethanediol (ethylene glycol) being preferred, and 1,6-hexanediol being more preferred. The polyols may be used alone or in combination of two or more kinds.

[0033] The crystalline polyester polyol (A1) is crystalline. The crystalline polyester polyol is a polyester polyol having an endothermic heat (hereinafter sometimes simply referred to as "endothermic heat") of 10 cal / g (40 J / g) or more in a melting curve measured at a heating rate of 10°C / min in differential scanning calorimetry (DSC) as specified in JIS K7121.

[0034] The number average molecular weight of the crystalline polyester polyol (A1) is preferably 1000 to 20000, more preferably 1500 to 10000, more preferably 1800 to 7000, more preferably 2000 to 6000, more preferably 2500 to 5000, more preferably 3000 to 4500, and more preferably 3200 to 4000. When the number average molecular weight of the crystalline polyester polyol (A1) is 1000 or more, the initial adhesiveness of the moisture-curable hot melt adhesive is improved, and the initial adhesiveness is improved. When the number average molecular weight of the crystalline polyester polyol (A1) is 20000 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced, which is preferable.

[0035] In the present invention, the number average molecular weight of a polyol refers to a value measured as follows. The number average molecular weight of a polyol can be measured by gel permeation chromatography (GPC). Specifically, a sample is dissolved in tetrahydrofuran (THF) to a concentration of 1.0 mass % to prepare a sample solution. The number average molecular weight of the polyol is measured by a refractive index detector using this sample solution and standard polystyrene as a reference by the GPC method.

[0036] As the measuring device, for example, a system consisting of a liquid delivery device LC-9A, a refractive index detector RID-6A, a column oven CTO-6A, and a data analyzer C-R4A (all manufactured by Shimadzu Corporation) can be used. As the GPC column, for example, three GPC-805 (exclusion limit 4 million) and one GPC-804 (exclusion limit 400,000) (all manufactured by Shimadzu Corporation) can be connected in this order. The measurement conditions are as follows: sample injection volume 25 μL (liters), eluent tetrahydrofuran (THF), liquid delivery volume 1.0 mL / min, and column temperature 45° C.

[0037] The hydroxyl value of the crystalline polyester polyol (A1) is preferably 20 to 50, more preferably 25 to 45, and particularly preferably 30 to 35. When the hydroxyl value of the crystalline polyester polyol (A1) is 20 or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved. When the hydroxyl value of the crystalline polyester polyol (A1) is 50 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced.

[0038] In the present invention, the hydroxyl value of a polyol means the number of milligrams of potassium hydroxide required to neutralize acetic acid bonded to hydroxyl groups when 1 g of the polyol is acetylated (JIS K0070:1992 2.1(5)). Specifically, it can be measured by acetylating the hydroxyl groups in the polyol with acetic anhydride and then titrating the unused acetic anhydride with potassium hydroxide (JIS K0070:1992 3.1 (neutralization titration method)).

[0039] In the polyol (A), the content of the crystalline polyester polyol (A1) is 15 to 35 mass%, preferably 18 to 33 mass%, and more preferably 20 to 30 mass%, when the total amount of the crystalline polyester polyol (A1), the microcrystalline polyester polyol (A2), the non-crystalline polyester polyol (A3) and the polyether polyol (A4) is taken as 100 mass%. When the content of the crystalline polyester polyol (A1) is 15 mass% or more, the initial adhesion of the moisture-curable hot melt adhesive is improved. When the content of the crystalline polyester polyol (A1) is 35 mass% or less, the normal adhesion of the moisture-curable hot melt adhesive is improved.

[0040] [Microcrystalline polyester polyol (A2)] The polyol (A) contains a microcrystalline polyester polyol (A2). The microcrystalline polyester polyol (A2) is a condensation polymer of a polycarboxylic acid and a polyol. That is, the microcrystalline polyester polyol (A2) is a polymer obtained by condensation polymerization of a polycarboxylic acid and a polyol through an ester reaction between a carboxyl group of the polycarboxylic acid and a hydroxyl group of the polyol.

[0041] The polycarboxylic acid is not particularly limited, and examples thereof include terephthalic acid, isophthalic acid, 1,5-naphthalic acid, 2,6-naphthalic acid, cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylenedicarboxylic acid, dodecamethylenedicarboxylic acid, etc., with adipic acid and terephthalic acid being preferred, and adipic acid being more preferred. The polycarboxylic acid may be used alone or in combination of two or more kinds.

[0042] The polyol is not particularly limited, and examples thereof include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, diethylene glycol, cyclohexanediol, etc., with 1,6-hexanediol and ethylene glycol being preferred, and 1,6-hexanediol being more preferred. The polyols may be used alone or in combination of two or more kinds.

[0043] The polyester polyol (A2) is microcrystalline. The microcrystalline polyester polyol (A2) is a polyester polyol having an endothermic heat of 2.5 cal / g (10 J / g) or more and less than 10 cal / g (40 J / g) in a melting curve measured at a temperature rise rate of 10° C. / min in differential scanning calorimetry (DSC) as specified in JIS K7121.

[0044] The number average molecular weight of the microcrystalline polyester polyol (A2) is 3000 to 6000, preferably 3000 to 5000, and more preferably 4000 to 4800. When the number average molecular weight of the microcrystalline polyester polyol (A2) is 3000 or more, the initial adhesive strength of the moisture-curable hot melt adhesive is improved. When the number average molecular weight of the microcrystalline polyester polyol (A2) is 6000 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced, which is preferable.

[0045] The hydroxyl value of the microcrystalline polyester polyol (A2) is preferably 20 to 50, more preferably 20 to 40, and particularly preferably 20 to 30. When the hydroxyl value of the microcrystalline polyester polyol (A2) is 20 or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. When the hydroxyl value of the microcrystalline polyester polyol (A2) is 50 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced, which is preferable.

[0046] In the polyol (A), the content of the microcrystalline polyester polyol (A2) is 20 to 50 mass%, preferably 20 to 45 mass%, and particularly preferably 25 to 45 mass%, when the total amount of the crystalline polyester polyol (A1), the microcrystalline polyester polyol (A2), the non-crystalline polyester polyol (A3) and the polyether polyol (A4) is taken as 100 mass%. When the content of the microcrystalline polyester polyol (A2) is 20 mass% or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved. When the content of the microcrystalline polyester polyol (A2) is 50 mass% or less, the initial adhesiveness of the moisture-curable hot melt adhesive is improved.

[0047] [Non-crystalline polyester polyol (A3)] The polyol (A) contains a non-crystalline polyester polyol (A3). The non-crystalline polyester polyol (A3) is a condensation polymer of a polycarboxylic acid and a polyol. That is, the non-crystalline polyester polyol (A3) is a polymer obtained by condensation polymerization of a polycarboxylic acid and a polyol through an ester reaction between a carboxyl group of the polycarboxylic acid and a hydroxyl group of the polyol.

[0048] The polycarboxylic acid is not particularly limited, and examples thereof include terephthalic acid, isophthalic acid, phthalic anhydride, 1,5-naphthalic acid, 2,6-naphthalic acid, cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decamethylenedicarboxylic acid, and dodecamethylenedicarboxylic acid. Adipic acid, terephthalic acid, phthalic anhydride, and isophthalic acid are preferred, and adipic acid, terephthalic acid, and phthalic anhydride are more preferred. It is preferable that the polycarboxylic acid contains adipic acid, terephthalic acid, and phthalic anhydride. The polycarboxylic acid may be used alone or in combination of two or more kinds.

[0049] The polyol is not particularly limited, and examples thereof include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, diethylene glycol, cyclohexanediol, etc., with ethylene glycol and 1,6-hexanediol being preferred, and ethylene glycol being more preferred. The polyols may be used alone or in combination of two or more kinds.

[0050] The polyester polyol (A3) is non-crystalline. The non-crystalline polyester polyol (A3) is a polyester polyol having an endothermic heat of less than 2.5 cal / g (10 J / g) in a melting curve measured at a heating rate of 10° C. / min in differential scanning calorimetry (DSC) as specified in JIS K7121.

[0051] The number average molecular weight of the non-crystalline polyester polyol (A3) is 3000 to 6000, preferably 3100 to 5000, more preferably 3200 to 4000, and particularly preferably 3300 to 3800. When the number average molecular weight of the non-crystalline polyester polyol (A3) is 3000 or more, the initial adhesive strength of the moisture-curable hot melt adhesive is improved. When the number average molecular weight of the microcrystalline polyester polyol (A2) is 6000 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced.

[0052] The hydroxyl value of the non-crystalline polyester polyol (A3) is preferably 20 to 50, more preferably 20 to 40, and particularly preferably 20 to 35. When the non-crystalline polyester polyol (A3) has a hydroxyl value of 20 or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved. When the non-crystalline polyester polyol (A3) has a hydroxyl value of 50 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced.

[0053] In the polyol (A), the content of the amorphous polyester polyol (A3) is 10 to 50 mass%, preferably 11 to 40 mass%, more preferably 12 to 30 mass%, and particularly preferably 13 to 20 mass%, when the total amount of the crystalline polyester polyol (A1), the microcrystalline polyester polyol (A2), the amorphous polyester polyol (A3) and the polyether polyol (A4) is taken as 100 mass%. When the content of the amorphous polyester polyol (A3) is 10 mass% or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved. When the content of the amorphous polyester polyol (A3) is 50 mass% or less, the initial adhesiveness of the moisture-curable hot melt adhesive is improved.

[0054] [Polyether polyol (A4)] The polyol (A) contains a polyether polyol (A4). The polyether polyol (A4) is not particularly limited. The polyether polyol (A4) is preferably a polyether polyol represented by the general formula: HO-(R 3 -O)pH(wherein, R 3represents an alkylene group having 1 to 14 carbon atoms, and p is the number of repeating units and is a positive integer. A polymer containing a repeating unit represented by the formula (I) or a polyether polyol obtained by addition reaction of an alkylene oxide (e.g., ethylene oxide, propylene oxide, butylene oxide, isobutylene oxide, etc.) with an active hydrogen moiety of a bisphenol A molecular skeleton is preferred. The main chain skeleton of the polyether polyol (A4) may be composed of only one type of repeating unit, or may contain two or more types of repeating units, or may contain two or more types of polymer blocks. The polyether polyol (A4) may be used alone or in combination of two or more types.

[0055] The above general formula: HO-(R 3 The main chain skeleton of the polymer containing the repeating unit represented by [-(R 3 Examples of the -O)p- include polyethylene oxide, polypropylene oxide, polybutylene oxide, polytetramethylene oxide, polyethylene oxide-polypropylene oxide copolymer, and polypropylene oxide-polybutylene oxide copolymer. Among these, polypropylene oxide and polyethylene oxide-polypropylene oxide copolymer are preferred because they improve the normal adhesiveness of the moisture-curable hot melt adhesive.

[0056] As the polyether polyol obtained by addition reaction of alkylene oxide with the active hydrogen moiety of the bisphenol A molecular skeleton, a polyether polyol obtained by addition reaction of propylene oxide with the active hydrogen moiety of the bisphenol A molecular skeleton, or a polyether polyol obtained by addition reaction of ethylene oxide with the active hydrogen moiety of the bisphenol A molecular skeleton is preferred, since these improve the normal adhesion of the moisture-curing hot melt adhesive.

[0057] The number average molecular weight of the polyether polyol (A4) is 500 to 7000, preferably 600 to 6000, more preferably 650 to 5000, more preferably 700 to 4000, more preferably 750 to 3000, and particularly preferably 760 to 2500. When the number average molecular weight of the polyether polyol (A4) is 500 or more, the initial adhesiveness of the moisture-curable hot melt adhesive is improved, which is preferable. When the number average molecular weight of the polyether polyol (A4) is 7000 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced.

[0058] The hydroxyl value of the polyether polyol (A4) is preferably from 50 to 200, more preferably from 80 to 180, and particularly preferably from 100 to 150. When the hydroxyl value of the polyether polyol (A4) is 50 or more, the initial adhesiveness of the moisture-curable hot melt adhesive is improved. When the hydroxyl value of the polyether polyol (A4) is 200 or less, the melt viscosity of the moisture-curable hot melt adhesive can be reduced.

[0059] In the polyol (A), the content of the polyether polyol (A4) is 5 to 30 mass%, preferably 6 to 25 mass%, more preferably 7 to 20 mass%, and particularly preferably 8 to 15 mass%, when the total amount of the crystalline polyester polyol (A1), the microcrystalline polyester polyol (A2), the non-crystalline polyester polyol (A3) and the polyether polyol (A4) is taken as 100 mass%. When the content of the polyether polyol (A4) is 5 mass% or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved. When the content of the polyether polyol (A4) is 30 mass% or less, the initial adhesiveness of the moisture-curable hot melt adhesive is improved.

[0060] The polyol (A) may contain a polyol such as a polyester polyol other than the above polyester polyols, a polyether polyol other than the above polyether polyols, polycaprolactone, or a polycarbonate polyol, as long as the effect of the moisture-curable hot melt adhesive is not impaired.

[0061] [Polyisocyanate] The moisture-curing hot melt adhesive contains a urethane prepolymer, which is a reaction product of the polyol (A) and polyisocyanate. The urethane prepolymer is a product obtained by condensation polymerization of the polyol (A) and polyisocyanate while forming urethane bonds between the hydroxyl groups of the polyol (A) and the isocyanate groups of the polyisocyanate.

[0062] Examples of the polyisocyanate include diphenylmethane diisocyanate (MDI, 4,4', 2,4, 2,2', or a mixture thereof), carbodiimide-modified MDI, carbodiimidized diphenylmethane polyisocyanate, tolylene diisocyanate (TDI, 2,4, 2,6, or a mixture thereof), xylylene diisocyanate (XDI), 1,5-naphthalene diisocyanate (NDI), tetramethylxylene diisocyanate, phenylene diisocyanate, hexamethylene diisocyanate (HDI), da Examples of the polyisocyanate include immeric acid diisocyanate, norbornene diisocyanate, lysine diisocyanate, xylylene diisocyanate, tetramethyl xylylene diisocyanate, isophorone diisocyanate (IPDI), hydrogenated diphenylmethane diisocyanate (hydrogenated MDI), hydrogenated xylylene diisocyanate (hydrogenated XDI), cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, and isophorone diisocyanate. Polyisocyanates containing aromatic rings (e.g., benzene rings, naphthalene rings, etc.) are preferred. Among these, diphenylmethane diisocyanate and carbodiimide-modified MDI are preferred, and diphenylmethane diisocyanate is more preferred, since they improve the normal adhesion of the moisture-curable hot melt adhesive.

[0063] [Thermoplastic resin] The moisture-curable hot melt adhesive may contain a thermoplastic resin having a number average molecular weight of 7000 to 100000 in addition to the urethane prepolymer. When the moisture-curable hot melt adhesive contains a thermoplastic resin, the crystallinity of the moisture-curable hot melt adhesive is improved, the initial adhesion is improved, and the thermal stability of the moisture-curable hot melt adhesive is improved. Since the thermal stability of the moisture-curable hot melt adhesive is improved, it is preferable that the thermoplastic resin does not contain a urethane bond. Since the thermal stability of the moisture-curable hot melt adhesive is improved, it is preferable that the thermoplastic resin does not contain an isocyanate group.

[0064] The thermoplastic resin is not particularly limited, and examples thereof include acrylic resins, methacrylic resins, polyvinyl acetate, polystyrene derivatives, polyisobutene, polyolefins, polyalkylene oxides, polyamides, natural rubber, polybutadiene, polyisoprene, nitrobutadiene rubber (NBR), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), polystyrene-block-poly(ethylene-co-butylene)-block-polystyrene (SEBS), hydrogenated nitrobutadiene rubber (hydrogenated NBR), hydrogenated styrene-butadiene-styrene block copolymer (hydrogenated SBS), hydrogenated styrene-isoprene-styrene block copolymer (hydrogenated SIS), hydrogenated polystyrene-block-poly(ethylene-co-butylene)-block-polystyrene (hydrogenated SEBS). The thermoplastic resin may be a functional group modified product. The thermoplastic resin may be used alone or in combination of two or more kinds.

[0065] As the thermoplastic resin, since the initial adhesiveness is improved, an ethylene-vinyl acetate copolymer, an ethylene-butyl acrylate copolymer, an ethylene-methyl methacrylate copolymer, and polycaprolactone are preferable, and polycaprolactone is more preferable.

[0066] The number average molecular weight of the thermoplastic resin is preferably 7000 to 100000, more preferably more than 7000 and not more than 90000, more preferably 8000 to 80000, more preferably 10000 to 60000, and particularly preferably 20000 to 50000. When the number average molecular weight of the thermoplastic resin is 7000 or more, the initial adhesion of the moisture-curable hot melt adhesive is improved. When the number average molecular weight of the thermoplastic resin is 100000 or less, the compatibility with other compounds constituting the moisture-curable hot melt adhesive is improved, and gelation of the moisture-curable hot melt adhesive can be suppressed, which is preferable.

[0067] The number average molecular weight of the thermoplastic resin is a value measured in the same manner as the number average molecular weight of the polyol described above.

[0068] The content of the thermoplastic resin in the moisture-curable hot melt adhesive is preferably 0.5 to 30 parts by mass, more preferably 1 to 25 parts by mass, more preferably 3 to 20 parts by mass, and particularly preferably 5 to 15 parts by mass, relative to 100 parts by mass of the urethane prepolymer. When the content of the thermoplastic resin is 0.5 parts by mass or more, the initial adhesion of the moisture-curable hot melt adhesive is improved. When the content of the thermoplastic resin is 30 parts by mass or less, the compatibility with other compounds constituting the moisture-curable hot melt adhesive is improved, and gelation of the moisture-curable hot melt adhesive can be suppressed, which is preferable.

[0069] [Polymers having hydrolyzable silyl groups] The moisture-curable hot melt adhesive may contain a polymer having a hydrolyzable silyl group. The polymer having a hydrolyzable silyl group has at least one crosslinkable hydrolyzable silyl group in one molecule. The polymer having a hydrolyzable silyl group preferably does not contain an isocyanate group.

[0070] The hydrolyzable silyl group is a group in which a hydrolyzable group is bonded to a silicon atom, and examples of the hydrolyzable group include a hydrogen atom, a halogen atom, an alkoxy group, an acyloxide group, a ketoximate group, an amino group, an amide group, an acid amide group, an aminooxy group, a mercapto group, and an alkenyloxide group.

[0071] As the hydrolyzable silyl group, an alkoxysilyl group in which an alkoxy group is bonded to a silicon atom is preferred because it does not generate harmful by-products after the reaction. Examples of the alkoxy group include a methoxy group, an ethoxy group, a propyloxy group, an isopropyloxy group, a butoxy group, a tert-butoxy group, a phenoxy group, and a benzyloxy group, and the like. The methoxy group and the ethoxy group are preferred.

[0072] Examples of the alkoxysilyl group in which an alkoxy group is bonded to a silicon atom include trialkoxysilyl groups such as trimethoxysilyl group, triethoxysilyl group, triisopropoxysilyl group, and triphenoxysilyl group; dialkoxysilyl groups such as methyldimethoxysilyl group and methyldiethoxysilyl group; and monoalkoxysilyl groups such as dimethylmethoxysilyl group and dimethylethoxysilyl group. The polymer having a hydrolyzable silyl group may be used alone or in combination of two or more kinds.

[0073] The main chain of the thermoplastic resin having a hydrolyzable silyl group is preferably polyalkylene oxide, polyether polyol, (meth)acrylate polymer, polyolefin, and polyester, and more preferably polyalkylene oxide. The polyalkylene oxide is preferably polyethylene oxide, polypropylene oxide, polybutylene oxide, etc. The polyether polyol is preferably polyethylene glycol, polypropylene glycol, polytetramethylene glycol, random copolymers or block copolymers thereof, or polyoxyalkylene modified products of bisphenol A.

[0074] Examples of monomers constituting the (meth)acrylate polymer include alkyl (meth)acrylates in which the alkyl group has a carbon number of 1 to 12. The alkyl group more preferably has a carbon number of 2 to 8. In the present invention, (meth)acrylate means methacrylate or acrylate.

[0075] Examples of polyolefins include homopolymers or copolymers of α-olefins such as ethylene and propylene. Examples of polyolefins include polyethylene (e.g., low-density polyethylene (LDPE), medium-density polyethylene (MDPE), linear low-density polyethylene (LLDPE), metallocene-catalyzed polyethylene, high-density polyethylene (HDPE), etc.), polypropylene (PP), and ethylene-α-olefin copolymers (e.g., ethylene-propylene copolymers, etc.).

[0076] The polyester is preferably a polyester polyol, for example, a polyester polyol obtained by condensation polymerization of a glycol such as ethylene glycol, propylene glycol, neopentyl glycol, or tetramethylene glycol with a dicarboxylic acid such as terephthalic acid, isophthalic acid, sebacic acid, succinic acid, phthalic acid, or adipic acid.

[0077] The content of the polymer having a hydrolyzable silyl group is preferably 0.05 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and particularly preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the urethane prepolymer. When the content of the polymer having a hydrolyzable silyl group is 0.05 parts by mass or more, the normal adhesiveness of the moisture-curable hot melt adhesive is improved. When the content of the polymer having a hydrolyzable silyl group is 10 parts by mass or less, the initial adhesiveness of the moisture-curable hot melt adhesive is improved.

[0078] [Additives] The moisture-curable hot melt adhesive may contain tackifiers, oils, plasticizers, catalysts, stabilizers, fillers, antioxidants, light stabilizers, UV absorbers, colorants, flame retardants, fragrances, pigments, dyes, etc., to the extent that the effects of the adhesive are not impaired.

[0079] The tackifier is not particularly limited, and examples thereof include rosin-based resins, terpene-based resins, aliphatic petroleum resins, aromatic petroleum resins, etc. The tackifiers may be used alone or in combination of two or more kinds.

[0080] The ring and ball softening point of the tackifier is preferably 90 to 150° C., since this prevents dissolution from the moisture-curing hot melt adhesive at room temperature and allows the moisture-curing hot melt adhesive to be sufficiently melted when melting. The ring and ball softening point of the tackifier is a temperature measured in accordance with JIS K6863 (the measurement method involves supporting a ring filled with a sample horizontally in a glycerin bath, and measuring the temperature when a ball placed in the center of the sample touches the bottom plate).

[0081] The oil is not particularly limited, and examples thereof include aromatic components contained in known oils generally referred to as process oils, extender oils, softeners, etc., which serve as rubber softeners, naphthenic oils, paraffinic oils, etc. The oils may be used alone or in combination of two or more kinds.

[0082] The plasticizer is not particularly limited, and examples thereof include phosphate esters such as tributyl phosphate and tricresyl phosphate, phthalate esters such as dioctyl phthalate, fatty acid-basic acid esters such as glycerin monooleate, fatty acid dibasic acid esters such as dioctyl adipate, aliphatic esters such as butyl oleate and methyl acetyl ricinoleate, trimellitic acid esters, chlorinated paraffins, hydrocarbon plasticizers such as alkyl diphenyls and partially hydrogenated terphenyls, process oils, epoxy plasticizers such as epoxidized soybean oil and epoxy benzyl stearate, vinyl polymers obtained by polymerizing vinyl monomers, polyalkylene glycol esters such as diethylene glycol dibenzoate, triethylene glycol dibenzoate, and pentaerythritol esters. The plasticizers may be used alone or in combination of two or more.

[0083] The catalyst is used to improve the curing property of the moisture-curable hot melt adhesive. The catalyst is not particularly limited, and examples thereof include amine-based catalysts and tin-based catalysts. The catalyst may be used alone or in combination of two or more kinds.

[0084] As the amine catalyst, a morpholine compound is preferable. Specifically, 2,2'-dimorpholinodiethyl ether, bis(2,6-dimethylmorpholinoethyl)ether, bis(2-(2,6-dimethyl-4-morpholino)ethyl)-(2-(4-morpholino)ethyl)amine, bis(2-(2,6-dimethyl-4-morpholino)ethyl)-(2-(2,6-diethyl-4-morpholino)ethyl)amine, tris(2-(4 -morpholino)ethyl)amine, tris(2-(4-morpholino)propyl)amine, tris(2-(4-morpholino)butyl)amine, tris(2-(2,6-dimethyl-4-morpholino)ethyl)amine, tris(2-(2,6-diethyl-4-morpholino)ethyl)amine, tris(2-(2-ethyl-4-morpholino)ethyl)amine, tris(2-(2-ethyl-4-morpholino)ethylamine, and the like.

[0085] The tin catalyst is not particularly limited, and examples thereof include stannous acetate, dibutyltin dilaurate, dibutyltin dioctate, dibutyltin diacetate, dioctyltin dilaurate, dioctyltin dioctate, dioctyltin diacetate, stannous dioctanoate, etc. These may be used alone or in combination of two or more kinds.

[0086] When the moisture-curable hot melt adhesive contains a stabilizer, the thermal stability of the moisture-curable hot melt adhesive can be improved without decreasing the curing speed of the moisture-curable hot melt adhesive at room temperature.

[0087] The stabilizer is preferably an organic phosphorus stabilizer. Examples of the organic stabilizer include tricresyl phosphate, triethyl phosphate, tributyl phosphate, tris(2-ethylhexyl)phosphate, tributoxyethyl phosphate, triphenyl phosphate, octyldiphenyl phosphate, tris(isopropylphenyl)phosphate, cresyldiphenyl phosphate, triphenyl phosphite, triphenylphosphine, triphenylphosphine oxide, and aromatic phosphoric acid condensation ester.

[0088] The stabilizer is preferably a solid at room temperature (25° C.) As the stabilizer, triphenyl phosphate, triphenyl phosphine, triphenyl phosphine oxide, and aromatic phosphoric acid condensed ester are preferable.

[0089] The filler is not particularly limited, and examples thereof include silica, talc, clay, calcium carbonate, magnesium carbonate, anhydrous silicon, hydrated silicon, calcium silicate, titanium dioxide, carbon black, bentonite, organic bentonite, shirasu balloons, glass microballoons, organic microballoons such as phenolic resins and vinylidene chloride resins, polyvinyl chloride (PVC) powder, polymethyl methacrylate powder, and other resin powders. The fillers may be used alone or in combination of two or more.

[0090] The antioxidant is not particularly limited, and examples thereof include hindered phenol-based antioxidants, monophenol-based antioxidants, bisphenol-based antioxidants, polyphenol-based antioxidants, etc. The antioxidants may be used alone or in combination of two or more kinds.

[0091] The light stabilizer is not particularly limited, and for example, a hindered amine light stabilizer is preferable, and a hindered amine light stabilizer in which the amine portion is a tertiary amine is more preferable. Examples of the light stabilizer include N,N',N'',N'''-tetrakis-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine, decanedioic acid bis(2,2,6,6-tetramethyl-1(octyloxy)-4-piperidinyl)ester, a reaction product of 1,1-dimethylethyl hydroperoxide and octane, bis(1,2,2,6,6, -pentamethyl-4-piperidyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(1-octyloxy-2,2,6,6tetramethyl-4-piperidyl)sebacate, etc. The light stabilizers may be used alone or in combination of two or more kinds.

[0092] The ultraviolet absorbing agent is not particularly limited, and examples thereof include benzotriazole-based ultraviolet absorbing agents, benzophenone-based ultraviolet absorbing agents, etc. The ultraviolet absorbing agents may be used alone or in combination of two or more kinds.

[0093] [Moisture-curing hot melt adhesive] The method for producing the moisture-curable hot melt adhesive is not particularly limited. For example, the moisture-curable hot melt adhesive can be produced by adding a thermoplastic resin, additives, etc. to the urethane prepolymer produced in the manner described above, and then heating and melting the mixture to mix uniformly.

[0094] The melt viscosity of the moisture-curing hot melt adhesive at 120 ° C is preferably 10000 to 60000 mPa · s, more preferably 25000 to 55000 mPa · s, and more preferably 2800 to 50000 mPa · s. When the melt viscosity of the moisture-curing hot melt adhesive at 120 ° C is 10000 mPa · s or more, the initial adhesiveness of the moisture-curing hot melt adhesive is improved. When the melt viscosity of the moisture-curing hot melt adhesive at 120 ° C is 60000 mPa · s or less, the initial adhesiveness of the moisture-curing hot melt adhesive is improved. The melt viscosity of the moisture-curing hot melt adhesive at 120 ° C refers to the melt viscosity measured at a temperature of 120 ° C and a rotation speed of 20 rpm using a B-type viscometer in accordance with the Japan Adhesive Industry Association standard JAI-7-1999. It should be noted that a Brookfield viscometer is commercially available under the trade name "B-type Viscometer Digital Rheometer DVII (Rotor No. 29)," for example.

[0095] The initial creep property of the moisture-curable hot melt adhesive is preferably 30 mm or less, more preferably 20 mm or less, and particularly preferably 15 mm. The initial creep property of the moisture-curable hot melt adhesive is a value measured in the following manner.

[0096] The normal adhesive strength of the moisture-curing hot melt adhesive is preferably 30 N / inch or more, more preferably 40 N / inch or more, and particularly preferably 50 N / inch or more. The normal adhesive strength of the moisture-curing hot melt adhesive is preferably 100 N / inch or less. The normal adhesive strength of the moisture-curing hot melt adhesive is a value measured as follows.

[0097] The usage of the moisture-curing hot melt adhesive will be described. To use the moisture-curing hot melt adhesive, the moisture-curing hot melt adhesive is heated and melted, and then the molten moisture-curing hot melt adhesive is applied to a substrate (adherend) or a surface sheet (preferably a surface sheet). The surface sheet is bonded to the substrate via the moisture-curing hot melt adhesive. At this time, the moisture-curing hot melt adhesive maintains excellent initial adhesive strength over a long period of time. Therefore, the surface sheet can be reliably held by adhering it to the surface of the protruding corner of the substrate in a mountain-folded state that conforms to the shape of the substrate surface against the restoring force of the surface sheet. When the surface sheet is aligned along the recessed corner of the substrate surface in a valley-folded state, a peeling stress is applied to the surface sheet at the bent portion of the surface sheet in a direction in which the surface sheet moves away from the recessed corner of the substrate due to the restoring force of the surface sheet, but the surface sheet can be reliably held by adhering it along the recessed corner of the substrate against this peeling stress by the moisture-curing hot melt adhesive.

[0098] Furthermore, moisture-curing hot melt adhesives have excellent initial releasability, meaning that the surface sheet can be peeled off from the surface of the substrate immediately after bonding, for example within 5 to 15 minutes, without leaving any moisture-curing hot melt adhesive on the substrate surface. Therefore, if the bonding fails after the surface sheet is bonded to the substrate, the surface sheet can be easily peeled off from the substrate surface, making it easy to reuse the substrate, and reducing the amount of substrate waste due to bonding failures.

[0099] The moisture-curable hot melt adhesive is then left to stand for 120 to 200 hours, preferably in an environment at 20 to 25°C and a relative humidity of 50 to 60%, thereby hardening the moisture-curable hot melt adhesive and bonding the surface sheet integrally onto the substrate. EXAMPLES

[0100] The present invention will be described in more detail below using examples, but the present invention is not limited thereto.

[0101] The polyols, polyisocyanates and thermoplastic resins used in the examples and comparative examples are shown below.

[0102] [Polyol (A)] [Crystalline polyester polyol (A1)] Crystalline polyester polyol (A11) (manufactured by Evonik Degussa, trade name "Dynacol 7380", endothermic value: 25 cal / g, hydroxyl value: 31, number average molecular weight: 3500, condensation polymer of 1,10-decanedicarboxylic acid and 1,6-hexanediol, number of carbon atoms excluding carbon in carboxyl group in 1,10-decanedicarboxylic acid: 10, number of carbon atoms in 1,6-hexanediol: 6) Crystalline polyester polyol (A12) (Toyokuni Oil Mills, product name "HS 2H-350S", heat absorption: 25 cal / g, hydroxyl value: 32, number average molecular weight: 3500, condensation polymer of sebacic acid and 1,6-hexanediol, carbon number excluding carbon in carboxyl group in sebacic acid: 8, carbon number in 1,6-hexanediol: 6) Crystalline polyester polyol (A13) (Toyokuni Oil Mills, product name "HS 2H-451A", endothermic value: 18 cal / g, hydroxyl value: 25, number average molecular weight: 4500, condensation polymer of adipic acid and 1,6-hexanediol, carbon number excluding carbon in carboxyl group in adipic acid: 4, carbon number in 1,6-hexanediol: 6)

[0103] [Microcrystalline polyester polyol (A2)] Microcrystalline polyester polyol (A2) (Toyokuni Oil Mills, product name "HS 2H-458T", endothermic value: 6 cal / g, hydroxyl value: 25, number average molecular weight: 4500, condensation polymer of adipic acid, terephthalic acid, and 1,6-hexanediol)

[0104] [Non-crystalline polyester polyol (A3)] Non-crystalline polyester polyol (A3) (Toyokuni Oil Mills, product name "Polyol 2000", endothermic value: 2 cal / g, hydroxyl value: 32, number average molecular weight: 3500, condensation polymer of adipic acid, terephthalic acid, phthalic anhydride, and ethylene glycol)

[0105] [Polyether polyol (A4)] Polyether polyol (A41) (AGC Corporation, product name "Exenol 2020", polypropylene glycol, hydroxyl value: 56, number average molecular weight: 2000) Polyether polyol (A42) (ADEKA Corporation, product name "BPX55", a polyether polyol obtained by adding propylene oxide to the active hydrogen part of the bisphenol A molecular skeleton, hydroxyl value: 143, number average molecular weight: 800)

[0106] [Thermoplastic resin] Polycaprolactone (manufactured by Daicel Corporation, trade name "Placcel H4", number average molecular weight: 40,000, does not contain urethane bonds or hydrolyzable silyl groups)

[0107] [Polymers having hydrolyzable silyl groups] Polyalkylene oxide with hydrolyzable silyl group (Kaneka Corporation, product name "MS Polymer S-303", number average molecular weight: 8000, does not have urethane bond or isocyanate group)

[0108] [Polyisocyanate] ·4,4'-Diphenylmethane Diisocyanate

[0109] ( Example 1, Comparative Examples 1 to 10 ) Polyol (A) was fed in the prescribed amounts shown in Table 1 into a 3-liter, four-neck flask equipped with a stirring blade, and after heating to melt and mixing at 120°C, the flask was depressurized to 1 mmHg or less to dehydrate polyol (A). After purging the flask with nitrogen, polyol (A) was maintained at 80°C.

[0110] Table 2 shows the contents (mass %) of the crystalline polyester polyol (A1), the microcrystalline polyester polyol (A2), the non-crystalline polyester polyol (A3) and the polyether polyol (A4) in the polyol (A).

[0111] A predetermined amount of 4,4'-diphenylmethane diisocyanate was fed into the flask as the polyisocyanate, and the polyol (A) and 4,4'-diphenylmethane diisocyanate were reacted at 80°C for 3 hours under a nitrogen atmosphere to produce a urethane prepolymer. In the reaction between the polyol and the polyisocyanate, the ratio of the number of moles of hydroxyl groups in the polyol to the number of moles of isocyanate groups in the polyisocyanate (number of moles of isocyanate groups / number of moles of hydroxyl groups) is shown in Table 1.

[0112] While the obtained urethane prepolymer was kept at 80°C, a moisture-curable hot melt adhesive was produced by adding a predetermined amount of polycaprolactone shown in Table 1 to 100 parts by mass of the urethane prepolymer. The obtained moisture-curable hot melt adhesive was solid at 25°C.

[0113] The resulting moisture-curable hot melt adhesive was measured for melt viscosity, initial creep property (initial adhesion), initial peel property, normal adhesion property and folded-back portion retention property in the manner described below. The results are shown in Table 1.

[0114] [Melt Viscosity] The melt viscosity of the moisture-curing hot melt adhesive at 120°C was measured using a Brookfield viscometer (Brookfield product name "B-type viscometer digital rheometer DVII (rotor No. 29)") at a temperature of 120°C and a rotation speed of 20 rpm in accordance with the Japan Adhesive Industry Association standard JAI-7-1999.

[0115] [Initial creep properties (initial adhesion)] The moisture-curing hot melt adhesive was heated to 120° C. and melted. The molten moisture-curing hot melt adhesive was applied to the entire surface of a flat rectangular (150 cm long x 50 cm wide) polyolefin resin sheet with a thickness of 180 μm, to a coating thickness of 40 μm.

[0116] Next, a polyolefin resin sheet was placed on the surface of an aluminum plate-shaped substrate, the surface temperature of which was kept at 40°C, with the moisture-curing hot melt adhesive facing the substrate side, and then a rubber roll was rolled on the polyolefin resin sheet to produce a laminated sheet. A rectangular test piece 1 inch (2.54 cm) wide and 15 cm long was cut out from the laminated sheet.

[0117] One minute after the polyolefin resin sheet was laminated onto the surface of the aluminum substrate via a moisture-curing hot melt adhesive, the test piece was placed horizontally with the polyolefin resin sheet part facing downward, and a 100 g weight was attached to the longitudinal end of the polyolefin resin sheet part.

[0118] Ten minutes after a weight was attached to the polyolefin resin sheet portion of the test piece, the length of the polyolefin resin sheet portion peeled off from the aluminum substrate portion was measured.

[0119] [Folded part retention] The moisture-curing hot melt adhesive was heated to 120° C. and melted. The molten moisture-curing hot melt adhesive was applied to the entire surface of a flat rectangular (150 cm long × 50 cm wide) polyolefin resin sheet with a thickness of 180 μm to a coating thickness of 40 μm.

[0120] Next, an aluminum plate-shaped substrate was prepared with a surface temperature maintained at 40° C. The substrate had a rectangular parallelepiped shape with dimensions of 200 cm length × 60 cm width × 15 cm thickness.

[0121] A polyolefin resin sheet was placed on the top surface of the substrate (200 cm long x 60 cm wide) with the surface coated with the moisture-curable hot melt adhesive facing the substrate. At this time, the end of the polyolefin resin sheet was left protruding a specified length from the ridge where the top surface and side surface of the substrate intersect. Then, a rubber roll was rolled on the part of the polyolefin resin sheet placed on the top surface of the substrate.

[0122] Next, the protruding end portion of the polyolefin resin sheet extending beyond the ridge line of the substrate was bent away from the ridge line of the substrate and overlapped with the side surface of the substrate, and then a rubber roll was rolled over the protruding end portion of the polyolefin resin sheet overlapped with the side surface of the substrate to prepare a test specimen.

[0123] Ten minutes after the preparation of the test piece, the protruding end of the polyolefin resin sheet was visually observed to see whether it had peeled off from the side of the substrate, and a case where at least a portion of the protruding end had peeled off from the side of the substrate was judged to be "peeled off."

[0124] The protruding length of the protruding end of the polyolefin resin sheet was shortened from 10 mm at 1 mm intervals, and the presence or absence of peeling of the protruding end of the polyolefin resin sheet was measured in the above-mentioned manner, and the shortest length of the protruding end when peeling of the protruding end of the polyolefin resin sheet did not occur was defined as "folded-back portion fit." Note that in Comparative Example 2, peeling occurred even when the protruding length of the protruding end of the polyolefin resin sheet was 10 mm.

[0125] [Initial peelability] The moisture-curing hot melt adhesive was heated to 120° C. and melted. The molten moisture-curing hot melt adhesive was applied to the entire surface of a flat rectangular (150 cm long x 50 cm wide) polyolefin resin sheet with a thickness of 180 μm, to a coating thickness of 40 μm.

[0126] Next, a polyolefin resin sheet was fully laminated on the surface of an aluminum plate-shaped substrate with the surface temperature kept at 40°C so that the moisture-curing hot melt adhesive was on the substrate side, and then a rubber roll was rolled on the polyolefin resin sheet to produce a laminated sheet. After 10 minutes, the polyolefin resin sheet was peeled off from the surface of the plate-shaped substrate, and the peeling state was visually observed. When peeling occurred at the interface between the substrate and the moisture-curing hot melt adhesive and no moisture-curing hot melt adhesive remained on the substrate surface, it was referred to as "interface peeling", and when cohesive failure occurred in the moisture-curing hot melt adhesive, it was referred to as "cohesive failure".

[0127] [Normal adhesion] Test pieces were prepared in the same manner as in the measurement of the initial creep property. The test pieces were aged for one week in an atmosphere of 23°C and 55% relative humidity to allow the moisture-curing hot melt adhesive to cure with moisture.

[0128] Next, the polyolefin resin sheet was peeled off from the surface of the substrate at a peel angle of 180° and a peel speed of 50 mm / min, and the average peel strength at this time was measured as normal adhesive strength (N / inch). [Table 1]

[0129] [Table 2]

Claims

1. The composition comprises a urethane prepolymer which is a reaction product of a polyol including a crystalline polyester polyol which is a condensation polymer of a polycarboxylic acid having 2 to 14 carbon atoms excluding the carbon in the carboxy group and a polyol having 2 to 8 carbon atoms, a microcrystalline polyester polyol having a number average molecular weight of 3,000 to 6,000, a non-crystalline polyester polyol having a number average molecular weight of 3,000 to 6,000, and a polyether polyol having a number average molecular weight of 500 to 7,000, and a polyisocyanate and has an isocyanate group at its terminal; When the total amount of the crystalline polyester polyol, the microcrystalline polyester polyol, the non-crystalline polyester polyol, and the polyether polyol is taken as 100 mass %, the polyol contains 15 to 35% by mass of the crystalline polyester polyol, 20 to 50% by mass of the microcrystalline polyester polyol, 10 to 50% by mass of the non-crystalline polyester polyol, and 5 to 30% by mass of the polyether polyol; A moisture-curable hot melt adhesive comprising a polyalkylene oxide having a hydrolyzable silyl group.

2. The moisture-curable hot melt adhesive according to claim 1, characterized in that it contains a thermoplastic resin having a number average molecular weight of 7,000 to 100,000.

3. The thermoplastic resin contains at least one thermoplastic resin selected from the group consisting of ethylene-vinyl acetate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl methacrylate copolymer, and polycaprolactone. The moisture-curable hot melt adhesive according to claim 2.

4. The moisture-curable hot melt adhesive according to any one of claims 1 to 3, characterized in that the melt viscosity at 120 ° C. is 10,000 to 60,000 mPa · s.

Citation Information

Patent Citations

  • Multifunctional environment-friendly adhesive for 1-30 minutes

    CN110527480A

  • PUR hot melt adhesive for composite board and preparation method of PUR hot melt adhesive

    CN112322248A

  • High-initial-adhesion low-shrinkage high-strength polyurethane hot melt adhesive and preparation method thereof

    CN112552859A

  • Barium-group hexa-boride thin-film cold cathode and its manufacture

    JP1988032823A

  • Leathery sheet

    JP1988044877A